Structural suitability of bamboo for screenhouse construction in the humid tropics - Oluyimika Omobowale , Mobolaji; Akinsoji , Adisa; Alabi , Israel; Oluwasanmi Sijuade, Timothy; Mijinyawa , Yahaya (International Journal of Engineering and Technology, 2024)
The growing need of structures for controlled environment agriculture in the face of climate change cannot be overstated. While year-round crop production is possible in greenhouse farm-ing, procurement costs for conventional greenhouses is high. The use of readily-available local materials such as bamboo in the construction of greenhouses can help reduce construction costs. The objective of this study was therefore, to develop a bamboo-framed greenhouse (BfG) and to evaluate its structural suitability and micro-climate in comparison with an existing greenhouse (ExG) framed with mild steel. Climatic factors (temperature, humidity, and light) and vapour pressure deficit (VPD) were measured in BfG, ExG, and ambient. Using tomato as test crop, evaluation of crop performance was based on stem girth, number of leaves and yield, monitored in comparison with open field cultivation in a nearby plot. Temperature ranges in the BfG, ExG and ambient were 27.03 – 33.32 oC, 29.81 – 38.89 oC, and 25.27 – 28.33 oC, respectively, while relative-humidity ranged between 65.78–83.25%, 56.47–78.86% and 78.13–91.83%, respective-ly. The bamboo framed screenhouse performed satisfactorily and withstood several storm events for close to three years. Farmers in the humid tropics are advised that service life of bamboo-framed screenhouses is about two and half years.